2006
DOI: 10.1097/01.hjr.0000239476.79428.25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of demographic, dietary and other lifestyle factors on the prevalence of hyperlipidemia in Guangxi Hei Yi Zhuang and Han populations

Abstract: The current study reveals that there is a significant difference in the prevalence of hyperlipidemia and its risk factors between Hei Yi Zhuang and Han, which might result from different demographic characteristics, dietary habits and other lifestyle factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
98
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(107 citation statements)
references
References 30 publications
9
98
0
Order By: Relevance
“…Ruixing et al reported that the prevalence of hyperlipidemia was positively correlated with alcohol consumption [48]. We observed a strong positive association between alcohol consumption and dyslipidemia.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Ruixing et al reported that the prevalence of hyperlipidemia was positively correlated with alcohol consumption [48]. We observed a strong positive association between alcohol consumption and dyslipidemia.…”
Section: Discussionsupporting
confidence: 68%
“…Obesity not only increases the prevalence of dyslipidemia, but is also directly associated with HT, diabetes, and CHD [48]. Dyslipidemia in obesity may be the result of insulin resistance [49].…”
Section: Discussionmentioning
confidence: 99%
“…During the same period, a total of 540 subjects of Han Chinese who reside in the same county were also randomly selected from our previous stratified randomized cluster samples. 63 The average age of the subjects was 43.22 (SD, 16.52) years (range, 15-89 years). There were 262 males (48.52%) and 278 females (51.48%).…”
Section: Methodsmentioning
confidence: 99%
“…The individuals with TC greater than 5.17 mmol/L and/or TG greater than 1.70 mmol/L were defined as hyperlipidemic. 63 Hypertension was diagnosed according to the criteria of the 1999 World Health Organization-International Society of Hypertension Guidelines for the management of hypertension. 64 The diagnostic criteria of overweight and obesity were according to the Cooperative Meta-analysis Group of China Obesity Task Force.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation